The Lanchester Library — Building a Sustainable Library - Noon, Pat (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The award winning Lanchester Library is the largest deep plan naturally ventilated building in Europe and has consistently delivered significant energy savings compared to air conditioned buildings. The article provides some background to the design and explains the sustainable features of the building as well as describing how flexibility was built into the building to enable the library service to evolve in response to changing user needs.